Meta Pengaruh Keefektifan Media Pembelajaran Konkrit dan Digital terhadap Pemahaman Siswa Terkait Materi Sejarah Perumusan Pancasila Kelas 4 SDN Podorejo 03 - Alfin Ghafar Dwinanda; Slamet Andriansyah; Susilo Tri Widodo; Eva Nur Hidayah; Diyah Puwidayati (Mathematics Education Study Program, 2025)
Citizenship Education (PPKn) is a subject that has the aim of developing the attitudes and abilities of citizens in terms of skills, knowledge and attitudes. Providing material to be taught in Pancasila Education learning makes teachers try to adapt and create active learning, namely by using learning media. The results of interviews with class teachers and observations in class IV of SD N Podorejo 03 showed that in Pancasila Education lessons, students seemed less interested. This is reflected in their low activity and involvement during the learning process. During the open discussion session, only a handful of students showed enthusiasm for asking or answering questions. So we can see that the application of concrete learning media can improve students' understanding of the historical material on the formulation of Pancasila as a whole compared to the use of digital media in the form of learning vidios. This is because the implementation of learning using learning vidios is still hampered by learning facilities, so that not all students can watch the learning vidios well. The material coverage in the learning vidios is not yet comprehensive, some information is still incomplete. Apart from that, the level of student focus must be considered so that the information displayed in the learning vidio can be conveyed.